EFISIENSI BANK PEMBANGUNAN DAERAH: PENDEKATAN STOCHASTIC FRONTIER (Signifikan: Jurnal Ilmu Ekonomi, 2015)
The objective of this research is to analyze the efficiency rate at Islamic regional banks (BPD) in Indonesia, with case of 15 Islamic regional banks from 2008 – 2012. The method that used in this research is stochastic frontier analysis approach (SFA), which uses the input variable (such as human resources cost, administration cost, and other expenses) and the output variable is SFA (operational income). The average efficiency rate from 15 Islamic regional banks from 2008 – 2012 with SFA method is 53.21 percent and all of the Islamic regional banks doesn’t achieve the 100 percent efficiency. The most efficient banks is Islamic regional bank of Kalimantan Barat which the efficiency rate achieve 90.42 percent and the most inefficiency banks is Islamic regional bank of Sumatera Barat. The average efficiency rate from 2008-2012 is always increase each year. In 2008 the average efficiency rate only 33.57 percent and in the last of 2012 achieve 71.81 percent.DOI: 10.15408/sjie.v4i1.2291